Nosocomial infection caused by Methicillin- Resistant Staphylococcus aureus from different positions of Al-Fehaa Hospital-Basrah - H.Mehdi, Kuther; A.I.Almazini, Mehammed; A.I.Almazini, Muna (Al-Qadisiyah Journal of Pure Science, 2018)
Ninty bacteria were isolated from different areas in Al-Fehaa Hospital, this represents the operative theaters, wards and hallways of the hospital, the present studies showed that the prevalence of 27 Methecillin-resistant Staphylococcus aureus (MRSA) in nosocomial infections and their antibiotic resistant pattern to (Calvulanic acid, Amoxicillin, Clarithromycin, Vancomycin, Cefotaxin, Gentamycin)in concentrations (15, 20, 10, 30, 10, 30, 30)µg/ml at respectivily. The isolates of MRSA were dentified by biochemical tests and we noticed that all isolates of MRSA were resistant to Vancomycin (30µg/ml), Amoxicillin (30 µg/ml), Gentamycin (10µg/ml) and Clarithromycin(10 µg/ml).